TINGKAT SOLIDARITAS DAN KESADARAN MASYARAKAT DALAM PKN WARGA MENGHADAPI PERKEMBANGAN COVID-19 TERBARUKAN DI WILAYAH KELURAHAN MERUYUNG KECAMATAN LIMO KOTA DEPOK - Mulyadi; L, Kayus Leo; Satino; Wibisono, Hari; Putri, Fallen Annisa Aji (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
The hustle and bustle of the New Normal community activities of the Covid-19 pandemic which has forced the past two years to stay at home with all the limitations of community activities, returning to New Normal activities the community must remain obedient to government regulations with health protocols. The mutation of the renewable Covid-19 which is still worrying our society even to the point where those who are positively exposed to Covid 19 are still continuing in various regions of the archipelago, vaccines are still being given to people who have not fulfilled the third vaccine, the mutation of Covid-19 is continuously like developments in other countries, namely in England, America, Australia and other European countries, even those who are very worried about it are predicted that in early 2023 Covid-19 will mutate between countries more quickly. Implementation of Restrictions on Community Activities (PPKM) in anticipation of the permutation of the spread of the renewable Covid 19 by complying with health protocols washing hands regularly, wearing masks, keeping a distance is a very effective way to suppress the development of Covid-19. The Limo District area, especially the Meruyung sub-district, is located in the south of DKI Jakarta Province, a pandemic that has been experienced in the world and in Indonesia, the Meruyung Sub-district area is currently declared a green zone area with the implementation of New Normal or new normal without neglecting health protocol rules. Activities have returned to normal, especially in the Meruyung sub-district, Limo sub-district. Limo. And the Community Service (PKM) activities that we carry out with the Implementation method have a normal life expectancy as usual before Covid-19 and it is hoped that solidarity will continue to be carried out in a pluralistic society that is more effective with high awareness. This Abdimas carries the theme